1989
DOI: 10.1128/aem.55.9.2113-2118.1989
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of pentachlorophenol by polyurethane-immobilized Flavobacterium cells

Abstract: Polyurethane-immobilized Flavobacterium cells (ATCC 39723) degraded pentachlorophenol (PCP) at initial concentrations as high as 300 mg liter-'. The reversible binding of PCP to the polyurethane was shown to be important in the protection of the cells from inhibition of PCP degradation. The degradation activity of the bacteria was monitored for 150 days in semicontinuous batch reactors. The degradation rate dropped by about 0.6% per day. PCP was degraded in a continuous-culture bioreactor at a rate of 3.5 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(32 citation statements)
references
References 22 publications
(22 reference statements)
3
29
0
Order By: Relevance
“…At least, during the detoxification of 0.5 g/l of MCPB in the PU-bubble reactor the maximum degradation rate of MCPB increased up to Q,,, = 130 pmoles/l * h, in contrast to the reactor failure in the experiment without the PU-supply. A similar protective effect of another type of PU-foam (2% w/v) was reported for Flavobacterium ATCC 39723 concerning pentachlorophenol (O'REILLY and CRAWFORD 1989). Thus, due to the reversible binding of this substance 0.3 g/l of pentachlorophenol was found to be mineralized by PU-immobilized cells, while only 0.15 g/1 were degraded without PU.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…At least, during the detoxification of 0.5 g/l of MCPB in the PU-bubble reactor the maximum degradation rate of MCPB increased up to Q,,, = 130 pmoles/l * h, in contrast to the reactor failure in the experiment without the PU-supply. A similar protective effect of another type of PU-foam (2% w/v) was reported for Flavobacterium ATCC 39723 concerning pentachlorophenol (O'REILLY and CRAWFORD 1989). Thus, due to the reversible binding of this substance 0.3 g/l of pentachlorophenol was found to be mineralized by PU-immobilized cells, while only 0.15 g/1 were degraded without PU.…”
Section: Discussionsupporting
confidence: 76%
“…In the PU-supplied experiments the increase of the viable cell number of strain MH was always less than without PU due to a kind of association of the cells with the PU-foam. Thus, by the use of this PU-carrier no active immobilization procedure prior to the degradation experiments is required, in contrast to the operation with cells immobilized within the PU-foam (O'REILLY and CRAWFORD 1989) or with calcium alginate-encapsulated cells (REHG et al 1986, FERSCHL et al 1991. Furthermore, such PU-carriers are persistent to biodegradation, which is important for unsterile heterotrophic processes, whereas a lot of microorganisms are capable of utilizing natural polymers like alginate (KINOSHITA et al 199 1).…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of pentachlorophenol-degrading bacteria to activated sludge or natural waters stimulated degradation of pentachlorophenol [389,390]. The use of immobilized chlorophenol degrading bacteria has been demonstrated in several studies [391][392][393][394][395][396]. Immobilization increases the tolerance of bacteria to toxic substrates.…”
Section: Bioremediation Of Contami-nated Soil and Groundwatermentioning
confidence: 99%
“…Encapsulated bacteria are a safe and useful way to apply inoculants to soil environments in agriculture [20,21] and soil bioremediation [22,23]. During the early 1990s, reviews were published on methods of introducing bacteria into soil [24] and the use of solid carriers to introduce bacteria into soil [25].…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, studies on the use of alginate and U-carrageenan as carriers for microbial inoculants with lac-lux-marked Pseudomonas aeruginosa UG2Lr showed that these microorganisms survived up to 360 days at 4³C [26]. Encapsulated bacterial cells have also been used in bioremediation of pentachlorophenol [23] and phenols [22].…”
Section: Introductionmentioning
confidence: 99%